ETHNIC-MATH HOTS PADA KUE KERING HOMEMADE IEDUL FITRI 1443 HIJRIAH - Lenny Puspita Dewi; Novia Dwi Rahmawati (Cartesian: Jurnal Pendidikan Matematika, 2022)
Research and development (Research and Development) by producing products in the form of Mathematics Higer Order Thinking Skill (HOTS) questions based on culture and local wisdom on homemade pastries (ethnic-MathHOTS). The development model referred to by the researcher is the Analysis, Design, Development, Implementation and Evaluation (ADDIE) which was adapted into Analysis, Design, Development (ADD). The stages that the research team has done are currently only at the design stage, meaning that the design of the Mathematics Higer Order Thinking Skill (HOTS) questions based on culture and local wisdom on pastries (ethnic-MathHOTS) that will be made will be consulted with experts consisting of assessment experts. and material experts.